Шляхи підвищення енергоефективності роботи тепломасообмінних установок систем низькотемпературного комбінованого опалення при використанні альтернативних джерел енергії - Климчук, О. А.; Лужанська, Г. В.; Кандєєва, В. В.; Аксьонова, І. В.; Борохов, Іван Валерійович; Борохов, Иван Валерьевич; Borokhov, Ivan (My University, 2021)
UK: Актуальною проблемою сучасної економіки України в умовах економічної кризи є раціональне використання паливно-енергетичних ресурсів нашої країни. Одним з шляхів вирішення цієї задачі є акумулювання енергії. Згідно з напрямком Енергетичної стратегії держави на період до 2030 р, все більшої актуальності набувають розробка та впровадження комбінованих високоефективних систем низькотемпературного опалення на основі альтернативних джерел енергії з використанням тепло акумуляторів. Розглянуті питання щодо сумісного ефективного використання найбільш розповсюджених комбінаціях сумісного використання різних генераторів теплоти у запропонованих системах. Виконано дослідження існуючих схем роботи акумуляторів по різним типам приєднання теплоносія. В результаті отримано, що застосування перехресної схеми приєднання теплообмінної установки в системі комбінованого низькотемпературного опалення дозволяє домогтися максимально ефекту. EN: The urgent problem of the modern economy of Ukraine in the conditions of the economic crisis is the rational use of the fuel and energy resources of our country. One of the ways to solve this problem is energy storage. According to the direction of the Energy Strategy of the state for the period up to 2030, the development and implementation of combined highly efficient heat pump systems for low-temperature heating based on alternative energy sources using heat accumulators are becoming increasingly important. An important step in the design of a low temperature heating system is the selection of the type of heat pump and the capacity of the heat accumulator. To intensify the process of introducing innovative energy technologies, it is necessary to increase their profitability by significantly increasing the share of replacing traditional primary energy resources with alternative energy sources. The issues of joint effective use of the most common combinations of joint use of various heat generators in the proposed systems are considered. There are several schemes for the operation of heat accumulators for various types of coolant connection: parallel, cross, joint. In order to study the processes in heat exchange units of combined low-temperature heating systems with different schemes for connecting the source and consumer of heat, the SolidWorks software product was used. Using the Flow Simulation software package based on the SolidWorks software, the results of numerical modeling of thermal processes in the heat accumulator with visualization of the temperature field for the specified connection schemes were obtained In the course of the studies carried out on the existing schemes for the operation of batteries for various types of connection of the coolant, it was found that the use of a cross connection scheme for a heat accumulator installation is the most effective in a combined low-temperature heating system. Considering the above circumstances, it can be concluded that in order to harmonize the operation of the low-temperature heating system and consumers, it is recommended to install heat exchange units, namely heat accumulators or buffer tanks according to a cross-circuit connection of the coolant, while it is recommended to use combined low-temperature heating systems using alternative heat sources. RU: Актуальной проблемой экономики Украины в условиях экономического кризиса является рациональное использование топливно-энергетических ресурсов. Одним из путей решения является аккумулирование энергии. Согласно направлению Энергетической стратегии все большую актуальность приобретают разработка и внедрение комбинированных высокоэффективных систем низкотемпературного отопления на основе альтернативных источников энергии с использованием тепло аккумуляторов. Рассмотрены вопросы совместного эффективного использования наиболее распространенных комбинаций совместного использования различных генераторов теплоты в предложенных системах. Выполнены исследования существующих схем работы аккумуляторов по различным типам присоединения теплоносителя. В результате получено, что применение перекрестной схемы присоединения теплообменной установки в системе комбинированного низкотемпературного отопления позволяет добиться максимально эффекта.
Ways of increasing the energy efficiency of the operation of heat and mass exchange units of low temperature combined heating systems when using alternative energy sources
Пути повышения энергоэффективности работы тепломассообменных установок систем низкотемпературного комбинованого отопления при использовании альтернативных источников энергии
Keywords: теплові акумулятори; комбінована система низькотемпературного опалення; тепловий насос; heat accumulators; combined low temperature heating system; heat pump; тепловые аккумуляторы; комбинированная система низкотемпературного отопления; тепловой насос